2022
DOI: 10.1021/acsanm.2c01026
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen Loaded into Metal–Organic Framework Shells Coated on Fe3O4 Nanoparticles for the Removal of Protein-Bound Uremic Toxins in Blood

Abstract: When patients with chronic kidney disease receive hemodialysis, their protein-binding uremic toxins (PBUTs) accumulation rate in the blood is very high. One of the main representative substances is p-cresol sulfate (PCS). About 80% PCS integrates to the Sudlow site II of blood serum albumin through electrostatic interaction or van der Waals force. How to effectively remove PCS is very challenging. Here, we designed and prepared a kind of nanoremover for the removal of PCS. First, Fe3O4 nanoparticles were coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Zr-based MOFs are proven to demonstrate virtuous request prospects in the adsorption of uremic toxins. However, metal zirconium may be biologically toxic, which limits its commercial application [99]. (C) The dialysis procedure scheme is based on UAPNFM.…”
Section: Mofs As a Uremic Toxin Adsorbent For The Kidney Disease Trea...mentioning
confidence: 99%
“…Zr-based MOFs are proven to demonstrate virtuous request prospects in the adsorption of uremic toxins. However, metal zirconium may be biologically toxic, which limits its commercial application [99]. (C) The dialysis procedure scheme is based on UAPNFM.…”
Section: Mofs As a Uremic Toxin Adsorbent For The Kidney Disease Trea...mentioning
confidence: 99%
“…To be applicable as drug delivery systems, Zr-MOF materials must fulfil certain requirements: biocompatibility and an ordered pore network, narrow size distribution, and high surface area. Hybrid aerogel microparticles as drug delivery systems for cervical cancer chemotherapy can prevent extravasation [ 13 ] or remove protein-bound uremic toxins from blood, such as in the case of ibuprofen loaded onto metal–organic framework shells on Fe 3 O 4 nanoparticles [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…17−23 Among these literature studies, the MOF materials selected were mostly Zr-based MOFs, and Fe-based MOFs have also been mentioned recently. 17,19 The total adsorption of the sorbents was reported to leverage the hydrophobic and electrostatic interactions between uremic toxins and MOFs. 17 For example, Reynolds et al 17 synthesized MOF-808 and MIL-100(Fe) to compare their sorption capability toward uremic toxins with previously reported Zr-based MOFs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Clinical studies have demonstrated that PBUTs increase the risk of cardiovascular disease in patients with CKD . Searching for more efficient sorbents for the removal of PBUTs has received constant attention and various methods come into being. ,, Based on the host–guest hydrophobic interaction, electrostatic interaction, and pore size selectivity, diverse materials are subtly designed and constructed, including activated carbons, , zeolites, , composite membranes, and metal–organic frameworks (MOFs). Clinically, activated carbon-based and zeolite-based sorbents are the most mature and widely used ones. However, activated carbon, which solely relies on van der Waals force, lacks selectivity, resulting in the simultaneous removal of proteins, sodium/potassium ions, and other useful substances .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation